1924
DOI: 10.1002/zaac.19241410114
|View full text |Cite
|
Sign up to set email alerts
|

Über das salzartige Verhalten der Alkalialkyle in Metallalkylen als Lösungsmitteln

Abstract: Es konnte gezeigt werden, daß nicht nur das NaC2H5, sondern auch LiC2H5, KC2H5 und ebenso LiCH3, LiC6H5 und LiCH2C6H6 in ihren Zn(C2H5)2‐Losungen den elektrischen Strom leiten und somit darin salzartig konstituiert sind. Größere molare Leitfähigkeit, höherer Schmelzpunkt und gleichzeitige Beschränkung der Mischbarkeit mit dem Lösungsmittel ließen erkennen, daß der Salzcharakter, wie zu erwarten, um so ausgeprägter wurde, je elektropositiver das Alkalimetall war.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1938
1938
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…This concept proved to be very successful and still is applied until today. Beginning with benzyllithium, which owes its stability also to delocalization of its negative charge in the adjacent π system, a number of corresponding α‐substituted methyl groups has been developed (Scheme ). Another important example of phenyl‐substituted methyllithium is triphenylmethyllithium (LiCPh 3 ).…”
Section: Organolithium Compoundsmentioning
confidence: 99%
“…This concept proved to be very successful and still is applied until today. Beginning with benzyllithium, which owes its stability also to delocalization of its negative charge in the adjacent π system, a number of corresponding α‐substituted methyl groups has been developed (Scheme ). Another important example of phenyl‐substituted methyllithium is triphenylmethyllithium (LiCPh 3 ).…”
Section: Organolithium Compoundsmentioning
confidence: 99%
“…The X-ray crystal structure of a similar zincate anion confirmed the trigonal planar environment of the zinc atom, the counter-ion being a coordinated sodium cation. 75 In 1924 Hein et al 76 and many years later Gilman and Woods 77 prepared a zincate solution from diethylzinc and calcium metal. Kaufmann and co-workers 78 deduced from NMR spectroscopic investigations of such solutions a solvent-dependent equilibrium between the homoleptic compounds CaEt 2 and ZnEt 2 , the contact ion pair Ca 2+ ZnEt 4 2− with the intermediate Et-Ca(l-Et) 2 Zn-Et, and the solvent-separated ion pair with isolated ZnEt 4 2− anions.…”
Section: Iii2 Zincates and Cuprates Of The Heavy Alkaline-earth Metalsmentioning
confidence: 99%
“…The phenomenon was first discovered by Hein [54] in 1924. He found that a mixture of diethylzinc and ethyl sodium forms a solution which is not inferior to 0.1 N aqueous potassium chloride solution in electrical conductivity.…”
Section: Anodic Processesmentioning
confidence: 95%